2022
DOI: 10.3390/brainsci12010098
|View full text |Cite
|
Sign up to set email alerts
|

OXTR Gene DNA Methylation Levels Are Associated with Discounting Behavior with Untrustworthy Proposers

Abstract: Individual differences in temporal and probabilistic discounting are associated with a wide range of life outcomes in literature. Traditional approaches have focused on impulsiveness and cognitive control skills, on goal-oriented personality traits as well as on the psychological perception of time. More recently, literature started to consider the role of social and contextual factors in discounting behavior. Between others, higher generalized trust in human beings and specific trust in people who will delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
3
10
1
Order By: Relevance
“…For both task, participants were also presented choice items in “proposer” blocks, which provided a face stimulus and were asked to imagine that the showed face was the person proposing the choice between the two options while having no role in potential money delivery (see Figure 1 ). The used facial stimuli were manipulated for gender (male and female) and for perceived trustworthiness level (trustworthy, neutral, and untrustworthy) resulting in six different blocks (for a similar procedure, see Anzani et al, 2022 ). Order of presentation of the seven blocks was randomized as well as items’ order within each block.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For both task, participants were also presented choice items in “proposer” blocks, which provided a face stimulus and were asked to imagine that the showed face was the person proposing the choice between the two options while having no role in potential money delivery (see Figure 1 ). The used facial stimuli were manipulated for gender (male and female) and for perceived trustworthiness level (trustworthy, neutral, and untrustworthy) resulting in six different blocks (for a similar procedure, see Anzani et al, 2022 ). Order of presentation of the seven blocks was randomized as well as items’ order within each block.…”
Section: Methodsmentioning
confidence: 99%
“…Also, others’ perceived untrustworthiness can also feel like a danger, triggering unpleasant feelings that impact intertemporal and risk decisions ( Harris, 2012 ; Koppel et al, 2017 ). By the way, in a recent paper on adult samples, it was not only reported that proposer’s facial perceived untrustworthiness is associated with higher temporal discounting rate therefore indicating lower preference toward reward’s postponing, but also that the same effect applies to subjects’ probability discounting, for which participants were asked to choose between smaller sure and larger but risky options and were aware that reward delivery system was based on randomness ( Anzani et al, 2022 ). This evidence indicating a lower propensity toward risk taking with untrustworthy proposers, even if in need of replication, seems to suggest the possibility that this effect of untrustworthiness on decision-making may be sustained by a more domain-independent and less deliberative underlying process than ever thought before.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxytocin plays an important role in forming social habits such as attachments (as between a mother and child) [ 140 ], in expressing optimism and self-appreciation, and in reducing levels of aggression, fear, and stress [ 141 ], and in trust-building. A medication based on oxytocin is often administered to people who suffered child abuse to restore social bonds and the ability to trust [ 142 , 143 ]. During a test when subjects were administered doses of oxytocin, these subjects perceived faces displayed to them in photographs as being relatively friendlier and more attractive compared to subjects from the control group, who administered a placebo [ 144 ].…”
Section: Human Emotions and Genotypementioning
confidence: 99%